A nonradioactive electrophoretic mobility shift assay for measurement of pregnane X receptor binding activity to CYP3A4 response element - Vavrova, Aneta; Vrzal, Radim; Dvorak, Zdenek (Electrophoresis, 2013)
The electrophoretic mobility shift assay (EMSA) is a method for the study of specific DNA–protein interactions in vitro. The pregnane X receptor (PRX) is a key xenobiotic sensor that regulates the expression of drug-metabolizing enzymes andmany other genes. Radiolabeled ³²P-DNA-probes had been used in studies of PXR-DNA interactions. There is an increasing need for nonradioactive assays, due to the health, safety and environmental issues. In the current study, we present a protocol for the nonradioactive electrophoretic mobility shift assay, allowing studying interactions between human PXR with promoter DNA sequences.
Keywords: Response Elements; retardační test; HeLa Cells; steroidní receptory; Electrophoretic Mobility Shift Assay; responzivní elementy; Molecular Probes; Pregnane X Receptor; Receptors, Steroid; Humans; cytochrom P-450 CYP3A; HeLa buňky; lidé; Cytochrome P-450 CYP3A; pregnanový X receptor; molekulární sondy